2017
DOI: 10.1016/j.molcel.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The SMX DNA Repair Tri-nuclease

Abstract: SummaryThe efficient removal of replication and recombination intermediates is essential for the maintenance of genome stability. Resolution of these potentially toxic structures requires the MUS81-EME1 endonuclease, which is activated at prometaphase by formation of the SMX tri-nuclease containing three DNA repair structure-selective endonucleases: SLX1-SLX4, MUS81-EME1, and XPF-ERCC1. Here we show that SMX tri-nuclease is more active than the three individual nucleases, efficiently cleaving replication forks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(155 citation statements)
references
References 61 publications
11
144
0
Order By: Relevance
“…168 We have found that S. cerevisiae SSEs Mus81, Rad1-Rad10, and Slx1-Slx4 are all important in causing fragility at the Flex1 structure-forming subregion of FRA16D. 36 The involvement of all of these components suggests that they are functioning in a SSE super complex as has been shown for the human complex in vitro 169 , and that one important target of SSEs at CFSs in human cells is forks stalled at DNA structures.…”
Section: Cleavage At Secondary Structures Within Cfss Is a Cause Ofmentioning
confidence: 82%
“…168 We have found that S. cerevisiae SSEs Mus81, Rad1-Rad10, and Slx1-Slx4 are all important in causing fragility at the Flex1 structure-forming subregion of FRA16D. 36 The involvement of all of these components suggests that they are functioning in a SSE super complex as has been shown for the human complex in vitro 169 , and that one important target of SSEs at CFSs in human cells is forks stalled at DNA structures.…”
Section: Cleavage At Secondary Structures Within Cfss Is a Cause Ofmentioning
confidence: 82%
“…Interestingly, deletion of the SLX4-interacting region of MUS81 broadens substrate specificity, allowing the complex to target much more easily also replication intermediates at perturbed forks (46). Serine 87 is within the region interacting with SLX4 and its phosphorylation makes MUS81 more prone to associate with SLX4, providing a mechanistic explanation to the unscheduled targeting by the MUS81 S87D protein of HJ-like and possibly other branched intermediates during replication.…”
Section: Discussionmentioning
confidence: 99%
“…single HJs and D-loop structures), are processed by a second mechanism which involves structure-selective endonuclease (SSE)-mediated resolution [31,32,39,40]. There are two genetically distinct resolution pathways: one is mediated by the SLX1–SLX4, MUS81-EME1 and XPF-ERCC1 (SMX) tri-nuclease complex [27,31,4146], and the other is mediated by GEN1 endonuclease [4750]. …”
Section: The Origin Of Hr-ufbsmentioning
confidence: 99%